PEMETAAN POTENSI DESA WISATA EDUKASI PETIK JERUK DI DESA PETUNGSEWU KABUPATEN MALANG - Baidawi, Muhammad; Wahono, Arif (FKIP Universitas Wisnuwardhana, 2023)
The purpose of this court program is to map the potential for orange picking educational tourism in Petungsewu Village, Dau District, Malang Regency. Methods for implementing the observation service program, mapping tourism potential, compiling potential maps, monitoring and feedback. From the results of the activities it was found that the potential in Petungsewu Village includes abundant citrus plantations, beautiful natural panoramas, cafes with natural concepts, abundant water sources, adequate rest areas for visitors, national and international schools. From this potential, Petungsewu Village can become a tourist village by developing orange plantations as a tourist spot for picking oranges, rest areas as displays to showcase processed citrus products and their derivatives, natural cafes as places to eat traditional food, abundant water can be used for tourist spots and watering land, educational institutions as places for comparative studies in teaching and learning processes and school management.